The effects of bioactive components from the rhizome of Salvia miltiorrhiza (Danshen) on the characteristics of Alzheimer's disease - Cheong-Meng Chong; Huanxing Su; Jin-Jian Lu; Yitao Wang (BMC, 2019)
Abstract Alzheimer's disease (AD) is a common human neurodegenerative disease, which is characterized by the progressive loss of memory and the cognitive impairment. Since the etiology of AD is still unknown, it is extremely difficult to develop the effective drugs for preventing or slowing the AD process. The major characteristics of AD such as amyloid β plaques, neurofibrillary tangles, mitochondrial dysfunction, and autophagy dysfunction are commonly used as the important indicators for evaluating the effects of potential candidate drugs. The rhizome of Salvia miltiorrhiza (known as 'Danshen' in Chinese), a famous traditional Chinese medicine, which is widely used for the treatment of hyperlipidemia, stroke, cardiovascular and cerebrovascular diseases. Increasing evidences suggest that the bioactive components of Danshen can improve cognitive deficits in mice, protect neuronal cells, reduce tau hyperphosylation, prevent amyloid-β fiber formation and disaggregation. Here we briefly summarize the studies regarding the effects of bioactive component from Danshen on those major characteristics of AD in preclinical studies, as well as explore the potential of these Danshen component in the treatment of AD.